Karakteristik dan Pengetahuan Petani Cabai Merah terhadap Penggunaan Pestisida Kimia: Studi Kasus di Kecamatan Payakumbuh, Kabupaten Lima Puluh Kota, Indonesia - Sofia Amelia; Mega Amelia Putri; Fedri Ibnusina (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2022)
Excessive use of conventional pesticides will impact the environment and health. These negative impacts can be minimized with the knowledge of farmers about the use of chemical pesticides. This study aims to see the description and the relationship between the characteristics of farmers with farmers' knowledge of the use of chemical pesticides. The research sample was determined using the slovin formula, which obtained 90 respondents using the accidental sampling method. Data collection in the field used a questionnaire with the likert scale method to get a score from the characteristics and knowledge of the respondents. The analytical tool used to see the relationship between characteristics and respondents' knowledge is spearman rank correlation. The results showed that the characteristics of the respondents were age 31 to 45 years (38%), male sex (98%), education last high school (37%), land area < 0.5 ha (71%), work experience < 5 years (43%). The level of knowledge of red chili farmers in the Payakumbuh Sub-district is in the high category. Characteristics of respondents who have a relationship with farmers' knowledge are age with a significance of -0.247 and last education with a significance value of 0.302. Characteristics that have no association with farmers' knowledge are gender, land area and work experience. The results of this study indicate that the knowledge possessed by farmers in using chemical pesticides is already high, but it is necessary to improve the indicators of knowing product information.